"An Arena Where Meaning and Identity Are Debated and Contested on a Global Scale": Narrative Discourses in British Museum Exhibitions, 1972–2013. (January 2015) - Francis, David
Abstract Following the so‐called narrative turn in the social sciences, museums have increasingly been conceptualized as narrative environments (MacLeod 2012). This narrative approach is characterized by a focus on museum exhibitions as spaces that tell stories rather than as repositories of knowledge (Roberts 1997). Despite the ubiquity of the term "narrative" in museums, relatively few studies have attempted to use literary theory to understand how these narrative spaces function. This paper attempts to apply some of the analytical models of the Russian literary theorist Mikhail Bakhtin to museum displays in order to examine how competing internal and external discourses shape exhibition narratives. This study looks at eight British Museum exhibitions beginning with Treasures of Tutankhamun in 1972 and ending with Hajj: Journey to the Heart of Islam in 2012. It explores how Bakhtin's theoretical concepts, including the "dialogic nature of discourse, " "heteroglossia" and the "carnivalesque, " can aid our critical understanding of museum displays as discursive spaces. External discourses often enter the museum unnoticed, regardless of authorial/curatorial intent, and are often impossible to keep out. However, by being critically aware of how discourse functions, museum professionals can use the techniques of literary theory to create innovative exhibitions that promote reflection and discussion about the connections between the historical past and the world in which we live today.